VD_FINDINFO Arrêt / 2017 / 815 vom 6. November 2017 - VD Tribunal cantonal (2017)
RENTE D'INVALIDITÉ, RÉVISIONPRESTATION D'ASSURANCE | 28 al. 1 LAI, 17 LPGA, 6 LPGA, 7 LPGA, 8 al. 1 LPGA, 88a al. 1 RAI